Neodymium-iron-boron magnet and preparation method thereof, high-radiation-resistance bonded neodymium-iron-boron magnet and application

By constructing an inner shielding layer and an outer protective layer on the surface of neodymium iron boron magnets and combining them with electron beam irradiation technology, the problem of magnetic performance attenuation of traditional neodymium iron boron magnets in high radiation environments has been solved. This has achieved a synergistic improvement in lightweighting, low-temperature molding, and high radiation resistance, making it suitable for key spacecraft components.

CN121122860APending Publication Date: 2025-12-12HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511265013.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Traditional neodymium iron boron magnets suffer severe magnetic performance degradation under high radiation environments. Existing technologies struggle to balance lightweight design, low-temperature molding, and high radiation resistance, failing to meet the long-term reliable operation requirements of spacecraft under harsh radiation conditions such as deep space exploration.

Method used

An inner shielding layer and an outer protective layer are constructed on the surface of a neodymium iron boron magnet. The neutron trapping effect of gadolinium and the gamma-ray scattering function of boron nitride are used to form an efficient tiered shield. Electron beam irradiation technology is combined to enhance the magnet's radiation resistance, and an adhesive is used to strengthen the interfacial bonding.

Benefits of technology

The prepared neodymium iron boron magnets maintain stable magnetic properties under high radiation environments, possess lightweight characteristics and low-temperature molding advantages, and are suitable for key spacecraft components, ensuring long-term reliable operation under irradiation doses of 1 mgy or higher.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005583025290000211
    Figure BDA0005583025290000211
  • Figure BDA0005583025290000221
    Figure BDA0005583025290000221
  • Figure BDA0005583025290000222
    Figure BDA0005583025290000222
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron magnet, a preparation method thereof, a high-radiation-resistance bonded neodymium-iron-boron magnet and application. The neodymium-iron-boron magnet is of a core-shell structure. The core-shell structure comprises an inner core, an inner shielding layer and an outer protection layer, wherein the inner shielding layer and the outer protection layer sequentially cover the surface of the inner core. Wherein the inner core comprises a neodymium iron boron magnetic material, the inner shielding layer comprises gadolinium oxide, and the outer protection layer comprises boride. According to the method, efficient cascade shielding of high-energy particles such as neutrons and gamma rays is formed through the nuclear physical shielding principle (the neutron capture effect of the gadolinium element and the gamma ray scattering function of boron nitride), the radiation resistance of the magnet is greatly improved, and the prepared neodymium-iron-boron magnet has the advantages of light weight and low-temperature forming; and the synergistic improvement of high radiation resistance and excellent magnetic performance can be met at the same time. The high-radiation-resistance bonded neodymium-iron-boron magnet prepared based on the neodymium-iron-boron magnet can keep stable magnetic performance in an extreme environment with an accumulated radiation dose of more than 1MGy.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of rare earth permanent magnet materials, and particularly relates to a neodymium iron boron magnet and a preparation method thereof, a high-irradiation-resistant bonded neodymium iron boron magnet and application. BACKGROUND

[0002] The annual cumulative radiation dose in the geosynchronous orbit is 10-100 kGy, and the deep space mission (such as Mars exploration) can reach 1 MGy. In this environment, the traditional magnet will have lattice distortion of magnetic powder, broken chain degradation of the binder and other situations, resulting in sharp attenuation of magnetic properties, and it is difficult to meet the long-term service requirement.

[0003] The prior art has the conditions of heavy dependence on heavy metals, easy hydrolysis and failure of traditional silane coupling agents under irradiation, and high process complexity, lacks a lightweight shielding scheme, and cannot meet the lightweight requirement of the spacecraft.

[0004] CN113450986A discloses a preparation method of a rare earth permanent magnet. 11 B isotope substitution R2Fe 14 B at least 85% of 10 B, and through processes such as alloy smelting, casting, hydrogen breaking, airflow milling, orientation pressing, sintering, aging treatment and mechanical processing, a magnet with certain radiation resistance is prepared. The scheme improves the anti-irradiation ability of the magnet by isotope substitution of 11 B isotope substitution of 10 B in neodymium iron boron to improve the anti-irradiation ability of the magnet, but its price is very expensive, and the process of accurate substitution is difficult to implement.

[0005] Therefore, it is a key technical requirement to be urgently broken through in the field of aerospace to develop a neodymium iron boron magnet with lightweight characteristics, low-temperature forming advantages, and high anti-irradiation and excellent magnetic properties. SUMMARY

[0006] In view of the deficiencies of the prior art, the purpose of the present application is to provide a neodymium-iron-boron magnet and a preparation method thereof, a high-irradiation-resistant bonded neodymium-iron-boron magnet and an application. The present application uses an anisotropic neodymium-iron-boron magnet as a substrate, and sequentially constructs an inner shielding layer and an outer protective layer on the surface thereof. By means of the synergistic effect of the two-layer structure, high-efficiency step shielding of high-energy particles such as neutrons and gamma rays is formed by the nuclear physical shielding principle (neutron capture effect of gadolinium element and gamma ray scattering function of boron nitride), which greatly improves the magnet's radiation resistance. The neodymium-iron-boron magnet prepared thereby has lightweight characteristics, low-temperature forming advantages, and can simultaneously satisfy the synergistic improvement of high-irradiation resistance and excellent magnetic performance. The high-irradiation-resistant bonded neodymium-iron-boron magnet based on the neodymium-iron-boron magnet can be stably used in key components such as space probes, satellite attitude control flywheels, space station motors, which are exposed to cosmic rays and high-energy particle environments for a long time, and can maintain stable magnetic performance in extreme environments with a cumulative irradiation dose of 1 MGy or more, providing key material support for the long-term reliable operation of spacecraft in harsh radiation conditions such as deep space exploration.

[0007] To achieve this purpose, the present application adopts the following technical solutions:

[0008] In a first aspect, the present application provides a neodymium-iron-boron magnet, which is a core-shell structure, and the core-shell structure comprises an inner core and an inner shielding layer and an outer protective layer successively coated on the surface of the inner core.

[0009] Preferably, the inner core comprises a neodymium-iron-boron magnetic material, the inner shielding layer comprises gadolinium oxide, and the outer protective layer comprises boride.

[0010] The present application uses an anisotropic neodymium-iron-boron magnet as a substrate, and sequentially constructs an inner shielding layer and an outer protective layer on the surface thereof. By means of the synergistic effect of the two-layer structure, high-efficiency step shielding of high-energy particles such as neutrons and gamma rays is formed by the nuclear physical shielding principle (neutron capture effect of gadolinium element and gamma ray scattering function of boron nitride), which greatly improves the magnet's radiation resistance. The neodymium-iron-boron magnet prepared thereby has lightweight characteristics, low-temperature forming advantages, and can simultaneously satisfy the synergistic improvement of high-irradiation resistance and excellent magnetic performance. The high-irradiation-resistant bonded neodymium-iron-boron magnet based on the neodymium-iron-boron magnet can be stably used in key components such as space probes, satellite attitude control flywheels, space station motors, which are exposed to cosmic rays and high-energy particle environments for a long time, and can maintain stable magnetic performance in extreme environments with a cumulative irradiation dose of 1 MGy or more, providing key material support for the long-term reliable operation of spacecraft in harsh radiation conditions such as deep space exploration.

[0011] Preferably, the particle size D50 of the neodymium-iron-boron magnetic material is 15-50 μm, for example, it can be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc.

[0012] Preferably, the gadolinium oxide comprises Gd2O3.

[0013] Preferably, the thickness of the inner shielding layer is 50-200 nm, for example, can be 50 nm, 100 nm, 150 nm or 200 nm, etc.

[0014] In the present application, the suitable thickness of the inner shielding layer is conducive to the high cross-section capture of neutrons, and the optimal absorption of neutrons is achieved.

[0015] Preferably, the boride comprises boron nitride.

[0016] Preferably, the thickness of the outer protective layer is 100-300 nm, for example, can be 100 nm, 200 nm or 300 nm, etc.

[0017] In the present application, the suitable thickness of the outer protective layer is conducive to the optimal γ-ray scattering and secondary particle blocking.

[0018] Preferably, the thickness ratio of the inner shielding layer to the outer protective layer is 1:(1-2), for example, can be 1:1, 1:1.33, 1:1.5, 1:1.75 or 1:2, etc.

[0019] In the present application, the suitable thickness ratio of the inner shielding layer to the outer protective layer is conducive to taking into account the protection effect of the inner shielding layer and the outer protective layer, and maintaining a certain magnetic flux loss and interface strength.

[0020] In a second aspect, the present application provides a preparation method of the neodymium-iron-boron magnet according to the first aspect, and the preparation method comprises the following steps:

[0021] Preparation of the inner core comprising neodymium-iron-boron magnetic material.

[0022] Sequentially forming the inner shielding layer and the outer protective layer on the surface of the inner core; wherein the inner shielding layer comprises gadolinium oxide, and the outer protective layer comprises boride.

[0023] Preferably, the preparation step of the inner core comprises:

[0024] Mixing the neodymium-iron-boron magnetic powder, the surface impurity removing agent and the surface passivation agent, and performing pretreatment to obtain the pretreated neodymium-iron-boron magnetic material.

[0025] Preferably, the mixing manner comprises:

[0026] Mixing the neodymium-iron-boron magnetic powder and the surface impurity removing agent under stirring at 50-70℃ (for example, can be 50℃, 60℃ or 70℃, etc.), then rinsing to pH 6.5-7 (for example, can be 6.5, 6.6, 6.7, 6.8, 6.9 or 7, etc.), and then mixing the rinsed neodymium-iron-boron magnetic powder and the surface passivation agent.

[0027] Preferably, the particle size D50 of the neodymium-iron-boron magnetic powder is 15-25 μm, for example, it can be 15 μm, 20 μm or 25 μm, etc.

[0028] Preferably, the surface decontaminant includes any one or a combination of at least two of hydrochloric acid solution, nitric acid solution or acetone solution. For example, the nitric acid solution can be dilute nitric acid solution.

[0029] Preferably, the surface passivation agent includes any one or a combination of at least two of hydrogen peroxide solution, zirconium-based passivation agent, titanium-based passivation agent or silane coupling agent. For example, the zirconium-based passivation agent can be hexafluorozirconic acid, sodium fluorozirconate, etc., the titanium-based passivation agent can be hexafluorotitanic acid, potassium fluorotitanate, etc., and the silane coupling agent can be KH550 or KH560, etc.

[0030] Preferably, the preparation step of the inner shielding layer includes:

[0031] (a) mixing gadolinium salt solution, organic complexing agent, pH adjusting agent and solvent to prepare gadolinium sol.

[0032] (b) mixing the inner core and the gadolinium sol, reacting, and then performing aging drying and crystallization treatment.

[0033] For example, the gadolinium salt in the gadolinium salt solution can be Gd(NO3)3·6H2O, etc.

[0034] Preferably, the mixing in step (a) is accompanied by stirring, and the temperature of the stirring is 50-70℃, for example, it can be 50℃, 60℃ or 70℃, etc.

[0035] Preferably, the mixing time in step (a) is 20-40 min, for example, it can be 20 min, 30 min or 40 min, etc.

[0036] Preferably, the solvent in step (a) includes alcohol and water in a volume ratio of (3-9):3, for example, the volume ratio can be 3:3, 5:3, 7:3 or 9:3, etc., and the alcohol can be ethanol, etc. The same applies to the solvent mentioned below.

[0037] Preferably, the concentration of the gadolinium salt solution in step (a) is 0.05-0.3 mol / L, for example, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L or 0.3 mol / L, etc.

[0038] Preferably, the organic complexing agent in step (a) includes acetylacetone solution.

[0039] Preferably, the concentration of the acetylacetone solution is 0.08-0.12 mol / L, for example, it can be 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.11 mol / L or 0.12 mol / L, etc.

[0040] In the present application, the acetylacetone solution with a specific concentration is added as an organic complexing agent, which is a key control means to achieve uniform and dense coating. Too high concentration will hinder the condensation and prevent the formation of a dense coating layer, and too low concentration will result in insufficient chelation and holes in the coating layer.

[0041] Preferably, the pH regulator in step (a) comprises ammonia water.

[0042] Preferably, the concentration of the ammonia water is 25-28 wt%, for example, it can be 25 wt%, 26 wt, 27 wt% or 28 wt%, etc.

[0043] Preferably, the pH of the mixed solution system in step (a) is 8.9-9.1, for example, it can be 8.9, 9 or 9.1, etc.

[0044] Preferably, the solid-liquid ratio of the core and gadolinium sol in step (b) is 1 g:(10-30) mL, for example, it can be 1 g:10 mL, 1 g:15 mL, 1 g:20 mL, 1 g:25 mL or 1 g:30 mL, etc.

[0045] In the present application, the appropriate solid-liquid ratio during the mixing of the core and gadolinium sol is beneficial to maintaining the viscosity of the system and obtaining an inner protective layer with appropriate thickness.

[0046] Preferably, the temperature of the reaction in step (b) is 78-82℃, for example, it can be 78℃, 79℃, 80℃, 81℃ or 82℃, etc.

[0047] Preferably, the aging and drying step in step (b) comprises:

[0048] The reaction product is placed in the dark, and then pre-dried and finally dried.

[0049] Preferably, the temperature of the pre-drying is 50-70℃, for example, it can be 50℃, 60℃ or 70℃, etc.

[0050] Preferably, the temperature of the final drying is 110-130℃, for example, it can be 110℃, 120℃ or 130℃, etc.

[0051] Preferably, the reaction time in step (b) is 5-7h, for example, it can be 5h, 6h or 7h, etc.

[0052] Preferably, the temperature of the crystallization treatment in step (b) is 550-650℃, for example, it can be 550℃, 600℃ or 650℃, etc.

[0053] Preferably, the time of the crystallization treatment in step (b) is 1.5-2.5h, for example, it can be 1.5h, 2h or 2.5h, etc.

[0054] Preferably, the preparation step of the outer protective layer comprises:

[0055] (i) mixing a boron source, a nitrogen source, a dispersing agent and a solvent to obtain a precursor solution.

[0056] (ii) mixing the material after the inner shielding layer is coated on the inner core and the precursor solution, and then performing a reaction and a nitriding treatment.

[0057] Preferably, the boron source in step (i) comprises boric acid.

[0058] Preferably, the nitrogen source in step (i) comprises urea.

[0059] Preferably, the dispersing agent in step (i) comprises polyvinylpyrrolidone.

[0060] Preferably, the mixing step in step (i) comprises:

[0061] The boron source is dissolved in the solvent to obtain a boron source solution, and then the nitrogen source and the dispersing agent are added in sequence.

[0062] Preferably, the molar concentration ratio of the boron source solution and the nitrogen source is 1:(2.5-3.5), for example, it can be 1:2.5, 1:3 or 1:3.5, etc.

[0063] Preferably, the concentration of the boron source solution is 0.4-0.6mol / L, for example, it can be 0.4mol / L, 0.5mol / L or 0.6mol / L, etc.

[0064] Preferably, the nitrogen source is added with stirring.

[0065] Preferably, the nitrogen source is added in batches to ensure that the reaction proceeds sufficiently.

[0066] Preferably, the amount of the dispersing agent added accounts for 0.05-0.15wt% of the total mass of the precursor solution, for example, it can be 0.05wt%, 0.1wt% or 0.15wt%, etc.

[0067] Preferably, the solid-liquid ratio of the material after the inner shielding layer coats the inner core and the precursor solution in step (ii) is 1g:(10-20)mL, for example, it can be 1g:10mL, 1g:12mL, 1g:14mL, 1g:16mL, 1g:18mL or 1g:20mL, etc.

[0068] In the present application, during the mixing process of the material after the inner shielding layer coats the inner core and the precursor solution, the suitable solid-liquid ratio is conducive to the adhesion of the precursor solution and helps to carry out the subsequent operation.

[0069] Preferably, the temperature of the reaction in step (ii) is 78-82℃, for example, it can be 78℃, 79℃, 80℃, 81℃ or 82℃, etc.

[0070] Preferably, the reaction time in step (ii) is 5-7h, for example, it can be 5h, 6h or 7h, etc.

[0071] Preferably, the nitrogenization treatment in step (ii) includes pre-nitrogenization and final nitrogenization performed in sequence.

[0072] Preferably, the atmosphere of the pre-nitrogenization is a nitrogen atmosphere.

[0073] Preferably, the temperature of the pre-nitrogenization is 250-350℃, for example, it can be 250℃, 300℃ or 350℃, etc., and the time is 0.5-1.5h, for example, it can be 0.5h, 1h or 1.5h, etc.

[0074] Preferably, the atmosphere of the final nitrogenization includes nitrogen and ammonia.

[0075] In the process of the final nitrogenization, the atmosphere is replaced by the combination of nitrogen and ammonia, which helps to solve the contradiction between the low efficiency of pure nitrogen nitrogenization and the high safety risk of pure ammonia, and realizes low-temperature and high-efficiency nitrogenization.

[0076] Preferably, the flow ratio of the nitrogen and ammonia is 1:(1.5-2.5), for example, it can be 1:1.5, 1:2 or 1:2.5, etc.

[0077] Preferably, the temperature of the final nitrogenization is 500-650℃, for example, it can be 500℃, 550℃, 600℃ or 650℃, etc.

[0078] Preferably, the time of the final nitrogenization is 1.5-2.5h, for example, it can be 1.5h, 2h or 2.5h, etc.

[0079] Preferably, the preparation method includes the following steps:

[0080] (1) Preparation of the inner core:

[0081] The neodymium iron boron magnetic powder with particle size D50 of 15-25 μm is mixed with a surface impurity removing agent at 50-70 °C, then rinsed to pH of 6.5-7, and then the rinsed neodymium iron boron magnetic powder is mixed with a surface passivation agent at 50-70 °C (for example, it can be 50 °C, 60 °C or 70 °C, etc.) for 0.5-1.5 h (for example, it can be 0.5 h, 1 h or 1.5 h, etc.), and finally vacuum dried to obtain the pretreated neodymium iron boron magnetic material; wherein the temperature of the vacuum drying is 110-130 °C (for example, it can be 110 °C, 120 °C or 130 °C, etc.), and the time is 1-3 h (for example, it can be 1 h, 2 h or 3 h, etc.).

[0082] (2) Preparation of the inner shielding layer:

[0083] (a) Dissolve the gadolinium salt in a solvent to obtain a gadolinium salt solution with a concentration of 0.05-0.3 mol / L, then add an organic complexing agent to the gadolinium salt solution under stirring at 50-70 °C for mixing for 20-40 min, and then add a pH adjusting agent to make the pH of the solution system 8.9-9.1 to prepare a gadolinium sol; wherein the organic complexing agent comprises an acetylacetone solution, and the pH adjusting agent comprises ammonia.

[0084] (b) Mix the inner core and the gadolinium sol according to a solid-liquid ratio of 1 g:(10-30) mL, then react at 78-82 °C and 190-210 rpm (for example, it can be 190 rpm, 200 rpm or 210 rpm, etc.) for 5-7 h, then age and dry the obtained reaction product, then dehydrate the reaction product in an inert atmosphere at 180-220 °C (for example, it can be 180 °C, 190 °C, 200 °C, 210 °C or 220 °C, etc.) for 0.5-1.5 h (for example, it can be 0.5 h, 1 h or 1.5 h, etc.), then heat at a rate of 4-6 °C / min (for example, it can be 4 °C / min, 5 °C / min or 6 °C / min, etc.) to 550-650 °C, and then crystallize for 1.5-2.5 h, and finally cool (the cooling rate is ≤10 °C / min, for example, it can be 10 °C / min, 8 °C / min, 5 °C / min, 3 °C / min or 1 °C / min, etc.) to obtain the material with the inner shielding layer coated on the inner core; wherein the protective gas of the reaction comprises nitrogen, and the inert atmosphere comprises a nitrogen atmosphere.

[0085] (3) Preparation of the outer protective layer:

[0086] (i) mixing a boron source and a solvent to obtain a boron source solution with a concentration of 0.4-0.6 mol / L, then adding urea to the boron source solution under stirring at 50-70℃ (for example, 50℃, 60℃ or 70℃, etc.), then adding a dispersant and performing ultrasonic dispersion to obtain a precursor solution; wherein the molar concentration ratio of the boron source solution to urea is 1:(2.5-3.5); the dispersant includes polyvinylpyrrolidone, and the amount of the dispersant added accounts for 0.05-0.15wt% of the total mass of the precursor solution.

[0087] (ii) mixing the material after the inner shielding layer is coated on the inner core and the precursor solution according to a solid-liquid ratio of 1g:(10-20)mL, then performing a reaction for 5-7h under the condition of 78-82℃ and 100-200rpm (for example, 100rpm, 150rpm or 200rpm, etc.), and then performing cooling after the reaction.

[0088] performing drying treatment on the cooled material, then performing pre-nitridation for 0.5-1.5h in a nitrogen atmosphere at 250-350℃, then replacing the nitrogen atmosphere with a combined atmosphere of nitrogen and ammonia with a flow ratio of 1:(1.5-2.5), and then performing final nitridation for 1.5-2.5h by increasing the temperature to 500-650℃ at a rate of 4-6℃ / min (for example, 4℃ / min, 5℃ / min or 6℃ / min, etc.), and finally performing cooling under the protection of an inert atmosphere (for example, argon, etc.) to obtain a neodymium-iron-boron magnet.

[0089] In a third aspect, the present application provides a high-radiation-resistant bonded neodymium-iron-boron magnet, which is prepared by mixing the neodymium-iron-boron magnet of the first aspect and a bonding agent.

[0090] Preferably, the bonding agent includes a radiation stabilizer, a functional filler and a photoinitiator.

[0091] In the present application, the photoinitiator is used for electron beam activated crosslinking. The photoinitiator can be, for example, diaryliodonium salt I-250, etc.

[0092] Preferably, the radiation stabilizer includes polyether ether ketone.

[0093] In the present application, polyether ether ketone contains a benzene ring conjugated structure, which can resist chain scission.

[0094] Preferably, the functional filler includes boron nitride nanosheet and silicon carbide whisker.

[0095] In the present application, boron nitride nanosheet is beneficial to improve the neutron shielding efficiency, and silicon carbide whisker can enhance the mechanical strength after irradiation.

[0096] Preferably, the mass ratio of the irradiation stabilizer, boron nitride nanosheet, silicon carbide whisker and photoinitiator is (75-85):(5-15):(3-7):(3-7), for example, the selected range of the irradiation stabilizer "75-85" can be 75, 80 or 85, etc., the selected range of the boron nitride nanosheet "5-15" can be 5, 10 or 15, etc., the selected range of the silicon carbide whisker "3-7" can be 3, 4, 5, 6 or 7, etc., and the selected range of the photoinitiator "75-85" can be 3, 4, 5, 6 or 7, etc.

[0097] Preferably, the thickness of the boron nitride nanosheet is <5nm, for example, it can be 4nm, 3nm, 2nm or 1nm, etc.

[0098] Preferably, the diameter of the silicon carbide whisker is 0.3-0.7μm, for example, it can be 0.3μm, 0.4μm, 0.5μm, 0.6μm or 0.7μm, etc.

[0099] Preferably, the aspect ratio of the silicon carbide whisker is greater than 20, for example, it can be 22, 25, 28 or 30, etc.

[0100] Preferably, the mixing method of the neodymium-iron-boron magnet and the binder comprises:

[0101] The neodymium-iron-boron magnet and the binder are mixed and molded, and then subjected to electron beam irradiation.

[0102] Preferably, the temperature of the mixing is 200-240℃, for example, it can be 200℃, 210℃, 220℃, 230℃ or 240℃, etc.

[0103] Preferably, the pressure of the molding is 80-120MPa, for example, it can be 80MPa, 90MPa, 100MPa, 110MPa or 120MPa, etc.

[0104] Preferably, the electron beam irradiation comprises pre-irradiation and post-irradiation performed in sequence, and the radiation dose of the pre-irradiation is less than that of the post-irradiation.

[0105] In the present application, the electron beam irradiation is performed in sequence of pre-irradiation and post-irradiation, wherein the purpose of the pre-irradiation is to induce active particles or peroxide capable of initiating main reaction outside the radiation field and to perform pre-crosslinking to improve melt strength, and the purpose of the post-irradiation is to strengthen interface bonding to generate Gd-O-C covalent bond. Therefore, the process of the electron beam irradiation and the design scheme of the aforementioned coating can deeply integrate the nuclear physics shielding principle (neutron capture effect of gadolinium element and γ-ray scattering function of boron nitride) and material interface engineering (electron beam induced formation of stable Gd-O-C bond), and break through the contradiction that the traditional scheme cannot simultaneously consider light weight, high radiation resistance and low temperature forming.

[0106] In a fourth aspect, the application provides a use of the high radiation resistance bonded Nd-Fe-B magnet according to the third aspect in the field of aerospace.

[0107] The numerical ranges recited herein include all values from and including the lower and upper values. This is true even if the values included in the lower or upper range are outside of the disclosed numerical ranges. The endpoints of the ranges recited in the specification are not included. The application recited herein is not limited to the specific examples described herein and includes any and all alternatives, modifications, equivalents, and combinations thereof within the scope of the appended claims.

[0108] Compared with the prior art, the application has the following beneficial effects:

[0109] (1) The application uses anisotropic Nd-Fe-B magnet as a substrate, and sequentially constructs an inner shielding layer and an outer protective layer on the surface of the substrate. By the synergistic effect of the two-layer structure, high-energy particles such as neutrons and gamma rays are efficiently shielded by the nuclear physics shielding principle (the neutron capture effect of gadolinium and the gamma ray scattering function of boron nitride), which greatly improves the radiation resistance of the magnet. The Nd-Fe-B magnet prepared by the application has the advantages of lightweight and low-temperature forming, and can simultaneously satisfy the synergistic improvement of high radiation resistance and excellent magnetic performance.

[0110] (2) The high radiation resistance bonded Nd-Fe-B magnet prepared based on the Nd-Fe-B magnet can be stably used in key components such as space probes, satellite attitude control flywheels, and space station motors that are exposed to cosmic rays and high-energy particle environments for a long time. It can maintain stable magnetic performance in extreme environments with a cumulative radiation dose of more than 1 MGy, providing key material support for the long-term reliable operation of spacecraft in harsh radiation conditions such as deep space exploration. DETAILED DESCRIPTION

[0111] The technical solutions of the application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the application and should not be regarded as specific limitations on the application.

[0112] Embodiment 1

[0113] The embodiment provides a Nd-Fe-B magnet, which is a core-shell structure, and the core-shell structure comprises an inner core and an inner shielding layer and an outer protective layer successively coated on the surface of the inner core.

[0114] The inner core is a Nd-Fe-B magnetic material with a particle size D50 of 20 μm, the inner shielding layer is a Gd2O3 layer with a thickness of 150 nm, and the outer protective layer is a boron nitride layer with a thickness of 200 nm; the thickness ratio of the inner shielding layer and the outer protective layer is 1:1.33.

[0115] The embodiment also provides a preparation method of the above-mentioned Nd-Fe-B magnet, which comprises the following steps:

[0116] (1) Preparation of the inner core:

[0117] 500 g of NdFeB powder with a particle size D50 of 20 μm was mixed with 2 L of a hydrochloric acid solution (5 wt% mass fraction) at 60°C under stirring (stirring rate of 300 rpm, with ultrasonic) for 10 min, then washed with deionized water until the pH was 6.5, and then the washed NdFeB powder was mixed with 2 L of a hydrogen peroxide solution (3 wt% mass fraction) at 60°C under stirring (stirring rate of 300 rpm) for 1 h, and finally vacuum dried to obtain a pretreated NdFeB magnetic material; wherein the temperature of the vacuum drying was 120°C, the time was 2 h, and the vacuum degree was 0.1 MPa; the moisture residue of the pretreated NdFeB magnetic material was ≤0.2%.

[0118] (2) Preparation of the inner shielding layer:

[0119] (a) 86.4 g of Gd(NO3)3·6H2O was dissolved in a solvent to obtain a gadolinium salt solution with a concentration of 0.2 mol / L, then 10 mL of a 0.1 mol / L acetylacetone solution was added dropwise to the gadolinium salt solution under stirring at 60°C for 30 min, and then 25 wt% ammonia water was slowly added dropwise until the pH of the solution system was 9 to prepare a gadolinium sol; wherein the solvent comprises ethanol and water in a volume ratio of 7:3.

[0120] (b) 500 g of the inner core was added to 10 L of the gadolinium sol according to a solid-liquid ratio of 1 g:20 mL, and was placed in a double-layer glass reaction kettle for condensation reflux, and was reacted at 80°C and 200 rpm (anchor stirring paddle stirring) for 6 h, and nitrogen gas with a flow rate of 0.5 L / min was introduced for protection during the reaction; after the reaction, the obtained reaction product was placed in a sealed container, and was placed in the dark at 25°C for 12 h, then was pre-dried in an oven at 60°C for 24 h, and the material was turned over twice a day, then was finally dried under vacuum at 0.08 MPa and 120°C for 6 h; after the drying was completed, the material was subjected to dehydration treatment in a tube furnace under a nitrogen atmosphere at 200°C for 1 h, the nitrogen flow rate was 10 L / min, then the temperature was increased to 600°C at a rate of 5°C / min, and the material was subjected to crystallization treatment for 2 h, and finally the material was cooled to 100°C to obtain a material with the inner shielding layer coated on the inner core; wherein during the crystallization treatment, the gas pressure was 0.1 MPa; and the cooling rate was 5°C / min.

[0121] (3) Preparation of the outer protective layer:

[0122] (i) 30.9 g of boric acid and 200 mL of solvent were mixed to obtain a boric source solution with a concentration of 0.5 mol / L, then 90.1 g of urea was added to the boric source solution in batches under stirring at 60°C, followed by the addition of 0.5 g of polyvinylpyrrolidone and ultrasonic dispersion (40 kHz, 15 min) to obtain a precursor solution; wherein the solvent comprises ethanol and water in a volume ratio of 1:1; the molar concentration ratio of the boric source solution to urea is 1:3; the addition amount of polyvinylpyrrolidone accounts for 0.1 wt% of the total mass of the precursor solution.

[0123] (ii) The material after the inner core was coated with the inner shielding layer was added to 7.5 L of the precursor solution according to a solid-liquid ratio of 1 g:15 mL, and a reaction was carried out in a PTFE reaction kettle at 80°C and 150 rpm for 6 h, during which the solution conductivity was detected every 2 h (the conductivity was stable at 1.8-2.0 mS / cm), and after the reaction, the material was quenched to 10°C in an ice water bath.

[0124] The quenched material was placed in a centrifuge and centrifuged for 10 min at a speed of 3000 rpm, and then dried in an oven at 80°C for 12 h, during which the material was turned over 3 times; then it was added to a tube furnace, pre-nitrided at 300°C in a nitrogen atmosphere for 1 h at a nitrogen flow rate of 5 L / min, and then the nitrogen atmosphere was replaced with a combined atmosphere of nitrogen and ammonia at a flow ratio of 1:2, and the temperature was increased to 600°C at a rate of 5°C / min for 2 h of final nitridation at an ammonia flow rate of 8 L / min; finally, it was cooled to 150°C under the protection of an argon atmosphere with a flow rate of 10 L / min to obtain a neodymium-iron-boron magnet.

[0125] The embodiment also provides a high radiation-resistant bonded neodymium-iron-boron magnet, which is prepared by mixing the neodymium-iron-boron magnet and the binder as described above.

[0126] The binder comprises polyether ether ketone, boron nitride nanosheet, silicon carbide whisker and photoinitiator in a mass ratio of 80:10:5:10; the photoinitiator is diaryliodonium salt I-250; the boron nitride nanosheet has a thickness of 2 nm, and the silicon carbide whisker has a diameter of 0.5 μm and an aspect ratio of 25.

[0127] The mixing method of the neodymium-iron-boron magnet and the binder comprises:

[0128] The neodymium-iron-boron magnet and the binder are mixed and molded, and then pre-irradiation and post-irradiation are sequentially performed.

[0129] The mixing temperature is 220°C, the molding pressure is 100 MPa, the pre-irradiation radiation dose is 50 kGy, and the post-irradiation radiation dose is 100 kGy.

[0130] Embodiment 2

[0131] The embodiment provides a neodymium-iron-boron magnet, which is a core-shell structure, and the core-shell structure comprises an inner core and an inner shielding layer and an outer protective layer which are sequentially coated on the surface of the inner core.

[0132] The inner core is a neodymium-iron-boron magnetic material with a particle size D50 of 15 μm, the inner shielding layer is a Gd2O3 layer with a thickness of 50 nm, and the outer protective layer is a boron nitride layer with a thickness of 100 nm; and the thickness ratio of the inner shielding layer to the outer protective layer is 1:2.

[0133] The embodiment further provides a preparation method of the neodymium-iron-boron magnet, and the preparation method comprises the following steps:

[0134] (1) preparing an inner core:

[0135] 500 g of neodymium-iron-boron magnetic powder (NdFeB powder) with a particle size D50 of 20 μm is mixed with 2 L of hydrochloric acid solution (5 wt%) at 50 ℃ under stirring (stirring rate: 300 rpm, with ultrasonic) for 10 min, and then the neodymium-iron-boron magnetic powder is washed with deionized water until the pH is 6.8; then the washed neodymium-iron-boron magnetic powder is mixed with 2 L of hydrogen peroxide solution (3 wt%) at 50 ℃ under stirring (stirring rate: 300 rpm) for 0.5 h, and finally vacuum drying is performed to obtain a pretreated neodymium-iron-boron magnetic material; wherein the temperature of the vacuum drying is 110 ℃, the time is 3 h, and the vacuum degree is 0.1 MPa; and the residual moisture of the pretreated neodymium-iron-boron magnetic material is ≤0.2%.

[0136] (2) preparing an inner shielding layer:

[0137] (a) Gd(NO3)3·6H2O is dissolved in a solvent to obtain a gadolinium salt solution with a concentration of 0.1 mol / L, then 10 mL of 0.08 mol / L acetylacetone solution is added dropwise into the gadolinium salt solution under stirring at 50 ℃, the time is 40 min, and then ammonia water with a concentration of 26 wt% is slowly added dropwise until the pH of the solution system is 8.9 to prepare a gadolinium sol; wherein the solvent comprises ethanol and water in a volume ratio of 7:3.

[0138] (b) 500 g of the inner core was added to 5 L of the gadolinium sol according to a solid-liquid ratio of 1 g: 10 mL, and was placed into a double-layer glass reaction kettle for condensation reflux, and was reacted at 78°C, 210 rpm (anchor stirring paddle stirring) for 7 h, and nitrogen was introduced at a flow rate of 0.5 L / min during the reaction for protection; after the reaction, the obtained reaction product was placed in a sealed container, and was placed at 25°C in the dark for 12 h, and was pre-dried in an oven at 60°C for 24 h, and was turned over twice a day, and then was finally dried under vacuum at 0.08 MPa, 120°C for 6 h; after the drying was completed, dehydration treatment was performed in a tube furnace at 180°C in a nitrogen atmosphere for 1.5 h, the nitrogen flow rate was 10 L / min, then the temperature was increased to 550°C at a rate of 4°C / min, crystallization treatment was performed for 2.5 h, and finally cooled to 100°C to obtain the material after the inner shielding layer coated the inner core; wherein, during the crystallization treatment, the gas pressure was 0.1 MPa; the cooling rate was 5°C / min.

[0139] (3) Preparation of the outer protective layer:

[0140] (i) Boric acid and 200 mL of a solvent were mixed to obtain a boric source solution with a concentration of 0.4 mol / L, then urea was added to the boric source solution in batches under stirring at 50°C, then polyvinylpyrrolidone was added and ultrasonic dispersion was performed (40 kHz, 15 min) to obtain a precursor solution; wherein, the solvent comprises ethanol and water in a volume ratio of 1:1; the molar concentration ratio of the boric source solution to urea is 1:2.5; the addition amount of the polyvinylpyrrolidone accounts for 0.05 wt% of the total mass of the precursor solution.

[0141] (ii) The material after the inner shielding layer coated the inner core was added to 5 L of the precursor solution according to a solid-liquid ratio of 1 g: 10 mL, and was reacted in a PTFE reaction kettle at 78°C, 200 rpm for 7 h, during which the solution conductivity was detected every 2 h (the conductivity was stabilized at 1.8-2.0 mS / cm), and after the reaction, the temperature was rapidly cooled to 10°C in an ice water bath.

[0142] The material after the rapid cooling was placed into a centrifuge, and was centrifugally separated for 10 min at a speed of 3000 rpm, and then was subjected to drying treatment in an oven at 80°C for 12 h, during which the material was turned over 3 times; then was added into a tube furnace, and was subjected to pre-nitridation in a nitrogen atmosphere at 250°C for 1.5 h, the nitrogen flow rate was 5 L / min, then the nitrogen atmosphere was replaced by a combined atmosphere of nitrogen and ammonia at a flow rate ratio of 1:1.5, and was subjected to final nitridation at a rate of 4°C / min to 500°C for 2.5 h, the ammonia flow rate was 8 L / min; finally, was cooled to 150°C under the protection of an argon atmosphere at a flow rate of 10 L / min to obtain a neodymium-iron-boron magnet.

[0143] The embodiment also provides a high radiation resistance bonded neodymium-iron-boron magnet prepared by mixing the neodymium-iron-boron magnet and the binder.

[0144] The binder comprises polyether ether ketone, boron nitride nanosheet, silicon carbide whisker and photoinitiator in a mass ratio of 80:10:5:10; the photoinitiator is diaryliodonium salt I-250; the boron nitride nanosheet has a thickness of 2 nm, and the silicon carbide whisker has a diameter of 0.3 μm and an aspect ratio of 25.

[0145] The mixing method of the neodymium-iron-boron magnet and the binder comprises:

[0146] The neodymium-iron-boron magnet and the binder are mixed and molded, and then are sequentially subjected to pre-irradiation and post-irradiation.

[0147] The mixing temperature is 200 ℃, the molding pressure is 80 MPa, the pre-irradiation radiation dose is 50 kGy, and the post-irradiation radiation dose is 100 kGy.

[0148] Embodiment 3

[0149] The embodiment provides a neodymium-iron-boron magnet, which has a core-shell structure comprising an inner core and an inner shielding layer and an outer protective layer successively coated on the surface of the inner core.

[0150] The inner core is a neodymium-iron-boron magnetic material with a particle size D50 of 35 μm, the inner shielding layer is a Gd2O3 layer with a thickness of 200 nm, and the outer protective layer is a boron nitride layer with a thickness of 300 nm; the thickness ratio of the inner shielding layer to the outer protective layer is 1:1.5.

[0151] The embodiment also provides a preparation method of the neodymium-iron-boron magnet, which comprises the following steps:

[0152] (1) preparing an inner core:

[0153] 500 g of neodymium-iron-boron magnetic powder (NdFeB powder) with a particle size D50 of 20 μm is mixed with 2 L of hydrochloric acid solution (5wt% in mass fraction) at 70 ℃ under stirring (stirring rate: 300 rpm, with ultrasonic assistance) for 10 min, and then is washed with deionized water until the pH is 7; then the washed neodymium-iron-boron magnetic powder is mixed with 2 L of hydrogen peroxide solution (3wt% in mass fraction) at 70 ℃ under stirring (stirring rate: 300 rpm) for 1.5 h, and finally is vacuum dried to obtain a pretreated neodymium-iron-boron magnetic material; wherein the vacuum drying temperature is 130 ℃, the vacuum drying time is 1 h, and the vacuum degree is 0.1 MPa; the moisture residue of the pretreated neodymium-iron-boron magnetic material is ≤0.2%.

[0154] (2) Preparation of the inner shielding layer:

[0155] (a) Dissolve Gd(NO3)3.6H2O in a solvent to obtain a gadolinium salt solution with a concentration of 0.3 mol / L, then add 10 mL of 0.12 mol / L acetylacetone solution dropwise into the gadolinium salt solution under stirring at 70°C for 20 min, and then slowly add ammonia water with a concentration of 28 wt% to the solution system until the pH is 9.1 to prepare a gadolinium sol; wherein the solvent comprises ethanol and water in a volume ratio of 7:3.

[0156] (b) According to a solid-liquid ratio of 1 g:30 mL, add 500 g of the inner core to 15 L of the gadolinium sol, and place it in a double-layer glass reaction kettle for condensation reflux, and perform a reaction at 82°C and 190 rpm (anchor stirring paddle stirring) for 5 h, and introduce nitrogen gas with a flow rate of 0.5 L / min for protection during the reaction; after the reaction, place the obtained reaction product in a sealed container, and after standing in the dark at 25°C for 12 h, pre-dry in an oven at 60°C for 24 h, turn the material twice a day, and then perform final drying under vacuum at 0.08 MPa and 120°C for 6 h; after drying, perform dehydration treatment in a tube furnace at 220°C in a nitrogen atmosphere for 0.5 h, with a nitrogen flow rate of 10 L / min, then increase the temperature to 650°C at a rate of 6°C / min, perform crystallization treatment for 1.5 h, and finally cool to 100°C to obtain the material after the inner shielding layer coats the inner core; wherein the gas pressure during the crystallization treatment is 0.1 MPa; and the cooling rate is 5°C / min.

[0157] (3) Preparation of the outer protective layer:

[0158] (i) Mix 30.9 g of boric acid and 200 mL of a solvent to obtain a boron source solution with a concentration of 0.6 mol / L, then add urea to the boron source solution in batches under stirring at 70°C, and then add polyvinylpyrrolidone and perform ultrasonic dispersion (40 kHz, 15 min) to obtain a precursor solution; wherein the solvent comprises ethanol and water in a volume ratio of 1:1; the molar concentration ratio of the boron source solution to urea is 1:3.5; and the addition amount of polyvinylpyrrolidone accounts for 0.15 wt% of the total mass of the precursor solution.

[0159] (ii) According to a solid-liquid ratio of 1 g:20 mL, add the material after the inner shielding layer coats the inner core to 10 L of the precursor solution, and perform a reaction in a PTFE reaction kettle at 82°C and 100 rpm for 5 h, during which the solution conductivity is detected every 2 h (the conductivity is stable at 1.8-2.0 mS / cm), and then quench to 10°C in an ice water bath after the reaction.

[0160] The quenched substance is put into a centrifuge, centrifugally separated for 10 min at a speed of 3000 rpm, and then dried in an oven at 80℃ for 12 h with 3 times of turning; then a tube furnace is added, pre-nitridation is carried out at 350℃ in a nitrogen atmosphere for 0.5 h with a nitrogen flow rate of 5 L / min, then the nitrogen atmosphere is replaced by a combined atmosphere of nitrogen and ammonia with a flow rate ratio of 1:2.5, and final nitridation is carried out at a rate of 6℃ / min to 650℃ for 1.5 h with an ammonia flow rate of 8 L / min; finally, it is cooled to 150℃ under the protection of an argon atmosphere with a flow rate of 10 L / min, to obtain a neodymium-iron-boron magnet.

[0161] The embodiment also provides a high-radiation-resistant bonded neodymium-iron-boron magnet, which is prepared by mixing the neodymium-iron-boron magnet and the binder.

[0162] The binder comprises polyether ether ketone, boron nitride nanosheet, silicon carbide whisker and photoinitiator at a mass ratio of 80:10:5:10; the photoinitiator is diaryliodonium salt I-250; the boron nitride nanosheet has a thickness of 2 nm, and the silicon carbide whisker has a diameter of 0.7 μm and an aspect ratio of 25.

[0163] The mixing method of the neodymium-iron-boron magnet and the binder comprises:

[0164] The neodymium-iron-boron magnet and the binder are mixed and molded, and then pre-irradiation and post-irradiation are sequentially performed.

[0165] The mixing temperature is 240℃, the molding pressure is 120 MPa, the pre-irradiation radiation dose is 50 kGy, and the post-irradiation radiation dose is 100 kGy.

[0166] Embodiment 4

[0167] The difference between the embodiment and embodiment 1 is that the solid-liquid ratio in step (b) is 1 g:10 mL.

[0168] The rest of the preparation method and parameters remain the same as those in embodiment 1.

[0169] Embodiment 5

[0170] The difference between the embodiment and embodiment 1 is that the solid-liquid ratio in step (b) is 1 g:30 mL.

[0171] The rest of the preparation method and parameters remain the same as those in embodiment 1.

[0172] Embodiment 6

[0173] The difference between the embodiment and embodiment 1 is that the solid-liquid ratio in step (ii) is 1 g:10 mL.

[0174] The rest of the preparation method and parameters are consistent with Example 1.

[0175] Example 7

[0176] The difference between this example and Example 1 is that the solid-liquid ratio in step (ii) is 1 g:20 mL.

[0177] The rest of the preparation method and parameters are consistent with Example 1.

[0178] Example 8

[0179] The difference between this example and Example 1 is that the solid-liquid ratio in step (b) or the solid-liquid ratio in step (ii) is adjusted so that the thickness ratio of the inner shielding layer and the outer protective layer is 1:2.5.

[0180] The rest of the preparation method and parameters are consistent with Example 1.

[0181] Example 9

[0182] The difference between this example and Example 1 is that the solid-liquid ratio in step (b) or the solid-liquid ratio in step (ii) is adjusted so that the thickness ratio of the inner shielding layer and the outer protective layer is 1:0.8.

[0183] The rest of the preparation method and parameters are consistent with Example 1.

[0184] Example 10

[0185] The difference between this example and Example 4 is that the solid-liquid ratio in step (b) is 1 g:5 mL.

[0186] The rest of the preparation method and parameters are consistent with Example 4.

[0187] Example 11

[0188] The difference between this example and Example 5 is that the solid-liquid ratio in step (b) is 1 g:35 mL.

[0189] The rest of the preparation method and parameters are consistent with Example 5.

[0190] Example 12

[0191] The difference between this example and Example 6 is that the solid-liquid ratio in step (ii) is 1 g:5 mL.

[0192] The rest of the preparation method and parameters are consistent with Example 6.

[0193] Example 13

[0194] The difference between this example and Example 7 is that the solid-liquid ratio in step (ii) is 1 g:25 mL.

[0195] The rest of the preparation method and parameters are consistent with Example 7.

[0196] Example 14

[0197] The difference between this example and Example 1 is that the pre-irradiation and post-irradiation are exchanged in the mixing method of the neodymium-iron-boron magnet and the binder.

[0198] The rest of the preparation method and parameters are consistent with Example 1.

[0199] Example 15

[0200] The difference between this example and Example 1 is that the pre-irradiation and post-irradiation are exchanged in the mixing method of the neodymium-iron-boron magnet and the binder.

[0201] The rest of the preparation method and parameters are consistent with Example 1.

[0202] Comparative Example 1

[0203] This comparative example provides a traditional neodymium-iron-boron magnet, and the preparation method comprises:

[0204] (1) Provide a neodymium-iron-boron raw material, then melt and powder the neodymium-iron-boron raw material, and sieve to obtain a neodymium-iron-boron magnetic powder.

[0205] (2) The neodymium-iron-boron magnetic powder is subjected to magnetic field orientation and compression molding to form a green body with anisotropy.

[0206] (3) The green body is subjected to sintering and heat treatment, and then subjected to mechanical processing, surface treatment and plating to form a zinc plating layer, thereby obtaining a neodymium-iron-boron magnet.

[0207] The rest of the preparation method and parameters of the high-irradiation-resistant bonded neodymium-iron-boron magnet are consistent with Example 1.

[0208] Comparative Example 2

[0209] The difference between this comparative example and Example 1 is that no boron nitride layer is provided, i.e. step (3) is not performed.

[0210] The rest of the preparation method and parameters are consistent with Example 1.

[0211] Comparative Example 3

[0212] The difference between this comparative example and Example 1 is that no Gd2O3 layer is provided, i.e. step (2) is not performed.

[0213] The rest of the preparation method and parameters are consistent with Example 1.

[0214] Performance test

[0215] I. The Nd-Fe-B magnets provided in the above examples and comparative examples were tested, including total coating rate, bonding strength, antioxidant, and neutron shielding rate.

[0216] The test results are shown in Table 1.

[0217] Table 1

[0218]

[0219]

[0220] II. The high radiation resistance bonded Nd-Fe-B magnets provided in the above examples and comparative examples were tested, and the test methods were ESAECS S-Q-70-71, NASAMSFC-SPEC-1448, and ASTM D1002.

[0221] The test results are shown in Table 2.

[0222] Table 2

[0223]

[0224] Analysis:

[0225] As can be seen from Tables 1 and 2, by taking anisotropic Nd-Fe-B magnets as substrates, and sequentially constructing an inner shielding layer and an outer protective layer on the surfaces thereof, and by means of the synergistic effect of the two-layer structure and in combination with a subsequent electron beam irradiation process, the nuclear physics shielding principle (neutron capture effect of gadolinium element and gamma ray scattering function of boron nitride) and material interface engineering (electron beam-induced formation of stable Gd-O-C bonds) are innovatively deeply integrated, and the technical bottleneck that the traditional scheme is difficult to balance between lightweight, high radiation resistance, and low-temperature forming is successfully broken through. The Nd-Fe-B magnets prepared thereby not only have the process advantages of lightweight characteristics and low-temperature forming, but also simultaneously realize the synergistic improvement of high radiation resistance performance, excellent mechanical strength, and outstanding magnetic performance. The high radiation resistance bonded Nd-Fe-B magnets made on the basis of the magnets can maintain stable magnetic performance in an extreme environment of more than 1 MGy cumulative irradiation dose, and provide key material support for the long-term reliable operation of spacecraft in harsh radiation conditions such as deep space exploration.

[0226] As can be seen from the comparison of Example 1 and Examples 4-5, higher or lower solid-liquid ratio is not conducive to the coating of the inner shielding layer, and will affect the radiation resistance performance of the magnet.

[0227] As can be seen from the comparison of Example 1 and Examples 6-7, higher or lower solid-liquid ratio is not conducive to the coating of the outer protective layer, and will affect the radiation resistance performance of the magnet.

[0228] It can be seen from the comparison of Example 1 with Examples 8-9 that if the thickness ratio of the inner shielding layer and the outer protective layer is too small, the primary photons penetrate, the scattered photons escape, resulting in insufficient thermal neutron absorption, decreased rigidity and increased cost; if the thickness ratio of the inner shielding layer and the outer protective layer is too large, the secondary electrons leak, the bremsstrahlung increases, resulting in penetration of fast neutrons, increased risk of creep and increased interfacial stress.

[0229] It can be seen from the comparison of Example 4 with Examples 10 and 5 with Example 11 that too large or too small solid-liquid ratio will result in poor coating quality of the inner shielding layer, which seriously affects the radiation resistance performance of the magnet.

[0230] It can be seen from the comparison of Example 7 with Example 12 and Example 8 with Example 13 that too large or too small solid-liquid ratio will result in poor coating quality of the outer protective layer, which seriously affects the radiation resistance performance of the magnet.

[0231] It can be seen from the comparison of Example 1 with Examples 14-15 that if pre-irradiation and post-irradiation are not performed, i.e., electron beam irradiation process is not performed, effective shielding protection cannot be generated; if post-irradiation is performed first and then pre-irradiation, the performance of the protective layer generated is low and cannot play a good protective role.

[0232] It can be seen from the comparison of Example 1 with Comparative Example 1 that the integrated scheme of the coating process and the synergistic enhancement of electron beam irradiation of the application can well improve the radiation resistance performance of the magnet and can guarantee a certain mechanical strength.

[0233] It can be seen from the comparison of Example 1 with Comparative Example 2 that if the boron nitride layer is not provided, it will result in failure to absorb gamma rays and a large decrease in mechanical strength and magnetic performance.

[0234] It can be seen from the comparison of Example 1 with Comparative Example 3 that if the Gd2O3 layer is not provided, it will result in failure to absorb neutrons and a large decrease in magnetic performance and mechanical strength.

[0235] It should be noted that the technical solutions of the application are illustrated by the above examples, but the application is not limited to the above examples, i.e., it does not mean that the application must rely on the above examples to be implemented. Those skilled in the art should understand that any improvement of the application, equivalent replacement of each raw material of the application product and addition of auxiliary ingredients, selection of specific methods, etc. fall within the protection scope and disclosure scope of the application.

Claims

1. A neodymium iron boron magnet, characterized in that, The neodymium iron boron magnet has a core-shell structure, which includes a core and an inner shielding layer and an outer protective layer that are sequentially covered on the surface of the core. The core comprises neodymium iron boron magnetic material, the inner shielding layer comprises gadolinium oxide, and the outer protective layer comprises borides.

2. The neodymium iron boron magnet according to claim 1, characterized in that, The particle size D50 of the neodymium iron boron magnetic material is 15-50 μm; Preferably, the gadolinium oxide comprises Gd₂O₃; Preferably, the thickness of the inner shielding layer is 50-200 nm; Preferably, the boride includes boron nitride; Preferably, the thickness of the outer protective layer is 100-300 nm; Preferably, the thickness ratio of the inner shielding layer to the outer protective layer is 1:(1-2).

3. A method for preparing a neodymium iron boron magnet as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: The core is prepared, the core comprising neodymium iron boron magnetic material; An inner shielding layer and an outer protective layer are sequentially formed on the surface of the core; wherein the inner shielding layer comprises gadolinium oxide and the outer protective layer comprises borides.

4. The preparation method according to claim 3, characterized in that, The kernel preparation steps include: Neodymium iron boron magnetic powder, surface impurity remover and surface passivator are mixed and pretreated to obtain pretreated neodymium iron boron magnetic material; Preferably, the particle size D50 of the neodymium iron boron magnetic powder is 15-25 μm; Preferably, the surface cleaning agent comprises any one or a combination of at least two of hydrochloric acid solution, nitric acid solution, or acetone solution; Preferably, the surface passivating agent includes any one or a combination of at least two of hydrogen peroxide aqueous solution, zirconium-based passivating agent, titanium-based passivating agent, or silane coupling agent.

5. The preparation method according to claim 3 or 4, characterized in that, The preparation steps of the inner shielding layer include: (a) Gadolinium salt solution, organic complexing agent, pH adjuster and solvent are mixed to prepare gadolinium sol; (b) The kernel and the gadolinium sol are mixed, reacted, and then aged, dried and crystallized. Preferably, the concentration of the gadolinium salt solution in step (a) is 0.05-0.3 mol / L; Preferably, the organic complexing agent in step (a) comprises an acetylacetone solution; Preferably, the pH adjuster in step (a) includes ammonia; Preferably, the pH of the mixed solution system described in step (a) is 8.9-9.1; Preferably, the solid-liquid ratio of the core and gadolinium sol in step (b) is 1 g:(10-30) mL; Preferably, the reaction temperature in step (b) is 78-82°C; Preferably, the reaction time in step (b) is 5-7 hours; Preferably, the temperature of the crystallization treatment in step (b) is 550-650°C; Preferably, the crystallization process in step (b) takes 1.5-2.5 hours.

6. The preparation method according to any one of claims 3-5, characterized in that, The preparation steps of the outer protective layer include: (i) The boron source, nitrogen source, dispersant and solvent are mixed to obtain a precursor solution; (ii) The material after the inner shielding layer covers the core is mixed with the precursor solution, reacted, and then nitrided. Preferably, the boron source in step (i) includes boric acid; Preferably, the nitrogen source in step (i) includes urea; Preferably, the dispersant in step (i) comprises polyvinylpyrrolidone; Preferably, the mixing step in step (i) includes: The boron source is dissolved in a solvent to obtain a boron source solution, and then a nitrogen source and a dispersant are added sequentially. Preferably, the molar concentration ratio of the boron source solution to the nitrogen source is 1:(2.5-3.5); Preferably, the solid-liquid ratio of the material after the inner shielding layer covers the core and the precursor solution in step (ii) is 1g:(10-20)mL; Preferably, the reaction temperature in step (ii) is 78-82°C; Preferably, the reaction time in step (ii) is 5-7 hours; Preferably, the nitriding treatment in step (ii) includes a pre-nitriding and a final nitriding performed sequentially; Preferably, the pre-nitriding atmosphere is a nitrogen atmosphere; Preferably, the pre-nitriding temperature is 250-350℃ and the time is 0.5-1.5h; Preferably, the atmosphere for final nitriding includes nitrogen and ammonia; Preferably, the flow rate ratio of nitrogen to ammonia is 1:(1.5-2.5); Preferably, the final nitriding temperature is 500-650°C; Preferably, the final nitriding time is 1.5-2.5 hours.

7. The preparation method according to any one of claims 3-6, characterized in that, The preparation method includes the following steps: (1) Kernel preparation: Neodymium iron boron magnetic powder with a particle size D50 of 15-25 μm was stirred and mixed with a surface impurity remover at 50-70℃, then rinsed until the pH reached 6.5-7. The rinsed neodymium iron boron magnetic powder and a surface passivating agent were then stirred and mixed at 50-70℃ for 0.5-1.5 h, and finally vacuum dried to obtain the pretreated neodymium iron boron magnetic material. The vacuum drying temperature was 110-130℃ and the time was 1-3 h. (2) Preparation of the inner shielding layer: (a) A gadolinium salt is dissolved in a solvent to obtain a gadolinium salt solution with a concentration of 0.05-0.3 mol / L. Then, an organic complexing agent is added to the gadolinium salt solution and mixed under stirring at 50-70°C for 20-40 min. Then, a pH adjuster is added to adjust the pH of the solution system to 8.9-9.1 to obtain gadolinium sol. The organic complexing agent includes acetylacetone solution, and the pH adjuster includes ammonia. (b) The core and the gadolinium sol are mixed at a solid-liquid ratio of 1g:(10-30)mL, and then reacted at 78-82℃ and 190-210rpm for 5-7h. After the reaction, the resulting reaction product is aged and dried, and then dehydrated at 180-220℃ in an inert atmosphere for 0.5-1.5h. Subsequently, the temperature is increased to 550-650℃ at a rate of 4-6℃ / min for 1.5-2.5h for crystallization. Finally, the mixture is cooled to obtain the material with the inner shielding layer covering the core. The protective gas in the reaction includes nitrogen, and the inert atmosphere includes a nitrogen atmosphere. (3) Preparation of the outer protective layer: (i) A boron source and a solvent are mixed to obtain a boron source solution with a concentration of 0.4-0.6 mol / L. Urea is then added to the boron source solution under stirring at 50-70°C, followed by the addition of a dispersant and ultrasonic dispersion to obtain a precursor solution. The molar ratio of the boron source solution to urea is 1:(2.5-3.5). The dispersant includes polyvinylpyrrolidone, and the amount of the dispersant added accounts for 0.05-0.15 wt% of the total mass of the precursor solution. (ii) The material after the inner shielding layer covers the core and the precursor solution are mixed at a solid-liquid ratio of 1g:(10-20)mL, and then the reaction is carried out at 78-82℃ and 100-200rpm for 5-7h. After the reaction, the mixture is cooled. The cooled material is dried, and then pre-nitrided in a nitrogen atmosphere at 250-350℃ for 0.5-1.5h. Subsequently, the nitrogen atmosphere is replaced with a combined atmosphere of nitrogen and ammonia at a flow ratio of 1:(1.5-2.5), and the temperature is increased to 500-650℃ at a rate of 4-6℃ / min for 1.5-2.5h for final nitriding. Finally, it is cooled under the protection of an inert atmosphere to obtain a neodymium iron boron magnet.

8. A highly radiation-resistant bonded NdFeB magnet, characterized in that, The high radiation-resistant bonded NdFeB magnet is prepared by mixing the NdFeB magnet described in claim 1 or 2 with a binder.

9. The high radiation-resistant bonded NdFeB magnet according to claim 8, characterized in that, The binder includes radiation stabilizers, functional fillers, and photoinitiators; Preferably, the radiation stabilizer comprises polyetheretherketone; Preferably, the functional filler comprises boron nitride nanosheets and silicon carbide whiskers; Preferably, the mass ratio of the radiation stabilizer, boron nitride nanosheets, silicon carbide whiskers and photoinitiator is (75-85):(5-15):(3-7):(3-7); Preferably, the method for mixing the NdFeB magnet and the binder includes: The neodymium iron boron magnets and binders are mixed and molded, and then subjected to electron beam irradiation; Preferably, the electron beam irradiation includes sequential pre-irradiation and post-irradiation, wherein the radiation dose of the pre-irradiation is less than the radiation dose of the post-irradiation.

10. The application of a high radiation-resistant bonded NdFeB magnet as described in claim 8 or 9 in the aerospace field.

Citation Information

Patent Citations

  • Rare earth permanent magnet and preparation method and application thereof

    CN113450986A